Good University Governance dan Kinerja Perguruan Tinggi - Talika Khairunisa; Ringgo Lufio Herdo; Zaki Irvan Mufid; Clara Dwi Santika; Meltya Anggraini; Fadhailah Aryani (Journal of Student Research, 2025)
This study aims to synthesize the results of previous research on Good University Governance (GUG) and Higher Education Performance through Systematic Literature Review (SLR). This research using SLR presents quantitative data to determine the development of the issue of GUG and Higher Education Performance. There are several parameters used, namely journal sources, variable mapping, theory, type of university and research approach. The results of this study show that there are 31 articles originating from accredited national and non-ranked national journals during the period 2020-2024. Topics related to internal audit, college performance, GUG, internal control, organizational commitment, and risk management.Agency Theory was the most widely used theory and the dominant use of quantitative methods in GUG and College Performance.Private Universities are the most widely researched universities on the issue of GUG and Higher Education Performance. This study contributes significantly to the map of previous research in a structured manner in the form of a list of independent, dependent, moderating, and mediating variables as determinants, consequences, and moderation-mediation so that through the relationship map, this study provides input for the topic of GUG and Higher Education Performance that still needs to be explored. This study has a limitation in that it is an interpretative study and therefore the findings are limited to i.